External validation of hemoglobin and neutrophil levels as predictors of the effectiveness of ipilimumab plus nivolumab for treating renal cell carcinoma - Hamamoto, Shuzo; Tasaki, Yoshihiko; Yamashita, Shimpei; Furukawa, Junya; Fujita, Kazutoshi; Tomida, Ryotaro; Miyake, Makito; Ito, Noriyuki; Iwamoto, Hideto; Sugiyama, Yosuke; Taguchi, Kazumi; Yasui, Takahiro (Frontiers in Oncology, 2024)
IntroductionPretreatment hemoglobin and neutrophil levels were previously reported to be important indicators for predicting the effectiveness of ipilimumab plus nivolumab (IPI + NIVO) therapy for renal cell carcinoma (RCC). Therefore, we aimed to validate this in a large external cohort.MethodsIn total, 172 patients with RCC who underwent IPI + NIVO treatment at a multicenter setting were divided into three groups according to their pretreatment hemoglobin and neutrophil levels (group 1: non-anemia; group 2: anemia and low-neutrophil; and group 3: anemia and high-neutrophil).ResultsGroup 1 showed better survival than groups 2 and 3 (overall survival: 52.3 vs. 21.4 vs. 9.4 months, respectively; progression-free survival: 12.1 vs. 7.0 vs. 3.4 months, respectively).DiscussionIn this large cohort, we validated our earlier observation that hemoglobin and neutrophil levels can be reliable predictors of the effectiveness of IPI + NIVO in advanced RCC. Thus, our approach may aid in selecting the optimal first-line therapy for RCC.